Individualization, Environment and Christianity (Challenges and Visions of New Ethics) - Zilova, Zuzana (Communications - Scientific letters of the University of Zilina, 2012)
The article reacts to new challenges in the phenomenon of individualization that are accompanied with the extreme scientific and technological growth. It focuses on controversial issues of civilization and traditional ethics: anthropocentrism, consumerism, individualism, and scientism. It stands for new ethics that would connect the good of man with the good of the environment.